1973
DOI: 10.1246/bcsj.46.1316
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of the CMC of Surfactants in Some Organic Solvents

Abstract: Extra absorption spectra appeared when 7,7,8,8-tetracyanoquinodimethane (TCNQ) was solubilized into surfactant organic solvent solutions above the critical micelle concentration (CMC). It was found also that extra absorption spectra appeared when iodine was solubilized into surfactant organic solvent solutions above the CMC. In the former case, the extra absorption spectra are attributed to TCNQ anion radical salts formed between TCNQ and the surfactants. In the latter, the extra absorption spectra are due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

1973
1973
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 17 publications
2
23
0
1
Order By: Relevance
“…Experimentalists, however, have succeeded in measuring transitions that are consistent with a step change from monomers to inverse micelles at a critical concentration [14][15][16][17][18][19][20][21][22]. Accurate and consistent values of CMCs for inverse micelle formation are lacking in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentalists, however, have succeeded in measuring transitions that are consistent with a step change from monomers to inverse micelles at a critical concentration [14][15][16][17][18][19][20][21][22]. Accurate and consistent values of CMCs for inverse micelle formation are lacking in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and consistent values of CMCs for inverse micelle formation are lacking in the literature. Several groups have used techniques as disparate as iodine solubilization and mercury interfacial tension to measure CMCs for AOT in different organic solvents, but the results are highly variable between the different studies [15,16,19,20,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The bulk solvent is known to affect various micellar properties, including the critical micelle concentration, [44] the size of w/o microemulsions, [45] and solvent penetration into the interface. [12] As a result, the properties of water molecules dissolved in the core can be influenced by the nature of the solvent.…”
Section: Influence Of the Oil On The Solvolysis Of Anisoyl Chloride (mentioning
confidence: 99%
“…As well, in the previously studied I,-AOT system (18) we found that AOT may act as a "n" donor, probably through the free electron pair on carbonyl gr0up.s present in the ester functions. Also, an n-n* EDA interaction have been proposed between AOT and 7,7,8,8-Tetracyanoquinodimethane (TCNQ) in several organic solvents (19). Thus, it may be that AOT competey with Naph in the association with TCNE.…”
Section: Effects Of the Aot Addition On Tcne-naph Interaction In The mentioning
confidence: 99%
“…(13). Moreover, although no Ks(2) values were calculated, it has been shown that AOT interacts so strongly wirh TCNQ (19) that the spectra of the anion radical of this acceptor is detected in reverse micelle systems.…”
Section: Eda Complexmentioning
confidence: 99%